WANPRESTASI PERJANJIAN LISAN ANTARA PENYEWA KIOS DAN LOS DI PASAR BARU PANGKALAN KERINCI KABUPATEN PELALAWAN - Mesy Yulandari; Hayatul Ismi; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Article 1313 of Code of Civil Law gives the formulation about “contract oragreement, an agreement is a deed with one name or more binding himself/herself to oneperson or more.” The occurance of default between the tenant and Market ManagementParty in which in the statement point number eight and ten saying it is forbidden to sell,rent, or lend the business place, stall or the place temporarily to other parties. The purposesof this research are to; first, find out the cause of default occurance of merchant oralagreement with the market management at Baru Market Pangkalan Kerinci, PelalawanRegency; second, find out the completion effort of oral agreement default of stall & businessplace tenancy between the merchant and the the management of Baru Market PangkalanKerinci Pelalawan Regency.The type of this research was Sociological research because the author directlyconducts research on the location the place being investigated in order to give complete andclear description on the problem being investigated.The result of the research and discussion shows that first, default occurance at BaruMarket Pangkalan Kerinci between the marchant and the management of the market inwhich the default or broken promise and negligent statement is in accordance with article1238 Code of Civil Law. Second, the completion way of the problem is by using negotiation.Third, the result of the agreement occured namely taking over the stall or the business placewhose the renter did default and even there is compensation. While the effort to overcomedefault is in the form of statement only. In the agreement of stall and business place tenancyat Baru Market Pangkalan Kerinci Pelalawan Regency is better to be written and not onlystatement and to be emphasized more on the related Articles. The creditor who rent thestrall or business place should be more explicit in implementing the agreement content andtake action on the tenant who disobey the agreement in line with the law and prevails thecompensation system thoroughly to give deterrent effect for default debtor.Keywords: Oral Agreement-Tenancy-Violating the agreement